Evaluación del Control Interno de Almacén y su incidencia en la rotación de inventarios de la empresa Ajeper del Oriente SA, en la ciudad de Tarapoto, periodo 2013 - Vera Cabrera, Katherine Danitza (2015)
Evaluate internal control warehouse proved to be of great relevance and determine their impact on inventory turns, helped the company AJEPER the East S.A, in Tarapoto, the 2013rd. The research method is the non- experimental observational ie systematic research where the researcher has no control over the independent variables because the events occurred or because they are inherently manipulative. In research Ex Post Facto changes in the independent variable already occurred and the investigator must be limited to the observation of existing situations given the inability to influence the variables and their effects as is the case of internal control store company AJEPER eastern SA. In this process the scheduled activities had a deficiency of 62 %, which at a rate of only 2 May activities are met , because of mishandling of internal control that is being developed in the current gesture and documents are delivered as invoices or tickets are only copies which does not allow logging to the system is not reliable for the area in charge of accounting and record documentation to improve these processes is important to the implementation of new procedures to reduce the risk and time of delivery to existing enterprise user areas. As for turnover rates of the company AJEPER mentioned that those are inappropriate because of its instability, which does not allow making correct decisions as to the dates of purchases, selling patterns and other factors that enable converted to cash the investment, this hurts meeting sales goals